Weathering product of granite as a possible source of strategic mineral - Ibrahim, Shaharin; Ashraf, Ahmadreza; Saion, Elias; Wood, Abdul Khalik; Wan Yusoff, Wan Abdullah (Springer, 2013)
Several soil samples and granite bedrock samples from Cameron Highlands were analyzed for its elemental concentration using instrumental neutron activation analysis. A total of 34 elements were identified and their concentrations were determined in a single analytical session. Enrichment factor of elemental concentration in the top soil were computed. The findings indicate certain elements were enriched that may facilitates economic beneficiation.